Verticalização em Londrina, Paraná (1950-2005): a produção do espaço urbano e seu desenvolvimento pelos edifícios verticais - Oura, Karen Yukie (2007)
Verticalization originates from the term vertical and is, in urban studies, commonly associated with buildings of multiple stories constructed for the purpose of increasing the value of a parcel of urban land by multiplying its potential for utilization. This research considers the change in the urban landscape of Londrina, Paraná, by means of a brief historical account, as well as a verification and analysis of the motives for which the city opted to construct tall buildings beginning with the Santo Antônio Building in 1950, through the year 2005, at which point the city showed a significant verticalization. The most vertical section of Londrina is the downtown area, since addressing residential demands in its neighborhoods has been possible only since legislative changes of the 1980s. This entire process is very significant because of the physical and ideological impact these buildings produce in the socio-economic structure of Londrina, as well as the changes they make in the visual character of space.